AI-Powered Location Intelligence: Revolutionizing Site Selection and Investment Decisions - Anil Kumar Reddy Avula (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This comprehensive article explores the transformative impact of artificial intelligence on location intelligence and site selection in the commercial real estate industry. The article examines how AI-powered systems are revolutionizing traditional approaches to property analysis, investment decisions, and operational efficiency across various real estate sectors. Through an examination of current implementations, benefits, and future trends, this analysis demonstrates how machine learning models, advanced analytics, and real-time data processing capabilities are enabling more accurate predictions, improved decision-making, and enhanced operational performance in the real estate industry. The article highlights the significant advancements in areas such as retail site selection, office space development, and industrial property optimization, while also addressing the quantifiable benefits and return on investment of AI implementation.